1997
DOI: 10.1152/ajpgi.1997.272.4.g785
|View full text |Cite
|
Sign up to set email alerts
|

Substance P and bradykinin stimulate plasma extravasation in the mouse gastrointestinal tract and pancreas

Abstract: Neurogenic inflammation is mediated by release of tachykinins from sensory nerves, which stimulate plasma extravasation from postcapillary venules. Because there are conflicting results regarding the importance of neurogenic inflammation in the gastrointestinal tract, we quantified plasma extravasation using Evans blue and identified sites of the leak using Monastral blue in the mouse. Substance P and bradykinin stimulated extravasation from postcapillary venules in the stomach, small and large intestine, panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 0 publications
4
81
0
3
Order By: Relevance
“…Capsaicin stimulates the release of SP and CGRP from primary sensory nerve endings in the gut (24) and thereby elicits an inflammatory response characterized by vasodilation and plasma extravasation (13). Consistently, intraveneous administration of SP in conscious rats stimulates the extravasation of plasma proteins in the duodenum, stomach, and pancreas (8,34). We have previously demonstrated that the lack of cutaneous capsaicin-induced plasma extravasation in Y1 Ϫ/Ϫ mice is caused by a failure of capsaicin-induced SP release (33).…”
Section: And Y1mentioning
confidence: 68%
“…Capsaicin stimulates the release of SP and CGRP from primary sensory nerve endings in the gut (24) and thereby elicits an inflammatory response characterized by vasodilation and plasma extravasation (13). Consistently, intraveneous administration of SP in conscious rats stimulates the extravasation of plasma proteins in the duodenum, stomach, and pancreas (8,34). We have previously demonstrated that the lack of cutaneous capsaicin-induced plasma extravasation in Y1 Ϫ/Ϫ mice is caused by a failure of capsaicin-induced SP release (33).…”
Section: And Y1mentioning
confidence: 68%
“…Substance P is a major mediator of neurogenic inflammation in several tissues including skin (20,21), cardiovascular tissue (6, 9, 25), cephalic structures (13,17,26), respiratory tract (7,15,27), genitourinary tract (23,30), and gastrointestinal tract (12,16,25,32). NKA has also been shown to play an important role in neurogenic inflammation in several conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We used Evans blue to measure extravasation of plasma proteins (4,15). Mice were anesthetized with xylazine (25 mg/kg i.m.)…”
Section: Methodsmentioning
confidence: 99%
“…SP mediates many aspects of neurogenic inflammation by interacting with the neurokinin-1 receptor (NK1R). Thus, SP interacts with the NK1R on endothelial cells of postcapillary venules in the airway and intestine to cause formation of gaps, which allows extravasation of plasma proteins (3,4).…”
mentioning
confidence: 99%